Extraction of wax from plants for possible commercial application - Wong, Jackie Teck Huat. (Universiti Malaysia Sarawak (UNIMAS), 2013)
Waxes are used in many industries such as cosmetics and personal care products. The market of wax industry is also expanding and growing at an encouraging rate. It is also noted that natural waxes are increasing in demand, especially plant-based waxes. The objective of this study is to extract wax from plants in order to detennine its chemical composition and possible commercial applications. Banana (Musa sp.) and yam (A/ocasia sp. and C%casia sp.) were used in this study. The waxes from these species were successfully extracted using n-hexane and their chemical compositions were determined. Wax of M. acuminate Colla ha a higher percentage of esters whereas wax of A. macrorrhiza has a higher percentage of hydrocarbons mostly alkanes. The possible commercial applications of the waxes based on their chemical compo ition were also estimated.